Indexing with Excel, Part 1. Basics, database properties, sorting. (1st June 2022) - Greulich, Walter
Abstract : At first glance, Excel is rather an unsuitable program for indexing, but if one takes a closer look and gains some experience with it, the picture changes. With Excel, some things are not possible that one is used to with dedicated indexing programs (DIPs), but after appropriate setup, Excel can serve very well as a supplement to DIPs, and it is even possible to write and output indexes with it. Only when one delves deeper into Excel does its full potential reveal itself, and that is enormous. To demonstrate the most important ways Excel can be used for indexing, a series of four articles is needed. This first article introduces the basics of Excel, then shows how to make a database out of an Excel spreadsheet – the most important step in making the program suitable for indexing. Finally, the topic of sorting is illuminated, showing what sorting in Excel means.